Analysis of Student Misconceptions in School Integer Theory Using Display Cards at Elementary School Level - Saskia, Arna (Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai-Nilai Islami); Vol 4 No 1 (2022): Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai Islami), 2021)
Learning mathematics is a branch of various arithmetic and is dubbed The Queen of Science. Misconceptions or misunderstandings of concepts in transferring information obtained by students into their framework are things that are often encountered in elementary schools. Misconceptions that occur in students will result in errors also for concepts at the next level. Several previous research results show that there are many misconceptions experienced by students in understanding concepts and solving integer problems. This study aims to analyze various misconceptions that are often done by students in solving integer problems and to improve student learning outcomes on integer material through positive and negative number card props in addition. The type of research used is qualitative research. which aims to get a deeper understanding of the forms of misconceptions experienced by students in solving problems related to integers so as to be able to describe the causes of misconceptions at MI Bustanul Ulum Batu City on integer material. The subjects used in this study were third grade students who had misconceptions about integers.